Angiostrongylus spp. in the nasal mucosa of Didelphis sp - Barbosa, Carolina Konkel; Orsi, Maysa Lopes; Takehara, Kenzo Lewandowski; Sousa, Renato Silva de (Brazilian Journal of Veterinary Pathology, 2025)
Nematodes of the genus Angiostrongylus are parasites capable of inhabiting the pulmonary arteries, heart, bronchioles, and mesenteric veins of various hosts. Opossum species of the genus Didelphis are considered synanthropic animals, cohabiting with humans and domestic animals and potentially disseminating zoonotic pathogens. This study aimed to report the changes caused by Angiostrongylus sp. nasal infection in Didelphis aurita and D. albiventris. Five animals were admitted to the Veterinary Hospital of the Federal University of Paraná, Curitiba, PR, Brazil, due to traumatic accidents. Three animals exhibited neurological clinical signs and, due to the severity of their condition, were euthanized or died. The necropsy of deceased animals revealed numerous adult worms in the nasal sinuses of all five individuals. Tissue sections, including nasal sinuses, were collected and submitted for histological evaluation. Adult parasites were recovered for generic morphological identification. Histopathological evaluation showed fibrinosuppurative and necrotic rhinitis along with sinusitis rhinitis and sinusitis with intralesional nematodes. Morphological identification demonstrated that the parasites belong to the genus Angiostrongylus (Metastrongylidae). This study is the first report of the genus Angiostrongylus sp. infecting the nasal mucosa of free-living opossums (Didelphis aurita and Didelphis albiventris).